Guidelines for the design of inclusive engineering education programs. - Mills, Julie E.; Ayre, Mary; Gill, Judith (Australian Learning and Teaching Council (ALTC), 2010)
This document consists of guidelines for the design of inclusive engineering education programs. It was produced as part of a project that aimed to produce resources to bring about sustainable change in the teaching and learning of engineering and construction management (E&CM): to increase the enrolment of women; to accommodate the increasingly diverse student body; and to improve retention and success of all students.